Incretin System: Recent Advances in Glucagon Like Peptide-1 and Dipeptidyl Peptidase-4 Inhibitors - Mahaseth, Rameshwar (Journal of Patan Academy of Health Sciences, 2015)
The endogenous incretins, glucose-dependent insulinotropic polypeptide and Glucagon-like peptide, are peptide hormones secreted from endocrine cells in the small intestine. Glucagon-like peptide-1 stimulates insulin and suppresses glucagon secretion, delays gastric emptying, and reduces appetite and food intake, which explains the positive effect of incretin mimetics on weight. The incretins have also been shown to have a sustained improvement in glycemic control over three years. A wide range of cardiovascular benefits have also been claimed, such as lowering of blood pressure and postprandial lipids. Clinical trials with the incretin mimetic exenatide and liraglutide show reductions in fasting and postprandial glucose concentrations, and haemoglobin A1c (1–2%), associated with weight loss (2–5 kg). The most common adverse event associated with Glucagon-like peptide-1 receptor agonists is nausea, which lessens over time. Orally administered Dipeptidyl Peptidase-4 inhibitors reduce hemoglobin A1c by 0·5–1·0%, with few adverse effects and no weight gain. These new classes of anti-diabetic agents also expand β-cell mass in preclinical studies. However, long-term clinical studies are still needed to determine the benefits of incretin for the treatment of type 2 diabetes. DOI: http://dx.doi.org/10.3126/jpahs.v1i1.13015 Journal of Patan Academy of Health Sciences. 2014 Jun;1(1):36-42